PENERAPAN MODEL GAME BASED LEARNING BERBANTUAN MEDIA EDPUZZLE UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V SDN 1 SOPAI - Tasik, Yeni; Salu, Benyamin; Salu Situru, Roberto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Studies for fifth-grade students at SDN 1 Sopai through the implementation of a Game Based Learning model assisted by Edpuzzle media. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages. The study was conducted in two cycles involving 15 students as research subjects. Data collection techniques included learning outcome tests, observations of teacher and student activities, and documentation. Data were analyzed using both quantitative and qualitative approaches. The results showed that the implementation of the Game-Based Learning model assisted by Edpuzzle media effectively improved students’ IPAS learning outcomes. This improvement was indicated by an increase in the mastery learning percentage from 40% in the pre-cycle to 46.67% in Cycle I and further increased to 80% in Cycle II. In addition, students’ learning motivation and active participation during the learning process also improved. Therefore, it can be concluded that the Game-Based Learning model assisted by Edpuzzle media is effective in improving IPAS learning outcomes for elementary school students.